2004
DOI: 10.1111/j.1478-3231.2004.0989.x
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete septal cirrhosis: an enigmatic disease

Abstract: We concluded that Incomplete septal cirrhosis is not a disease itself but it could be considered as a stage of progression and regression of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…NRH and incomplete septal cirrhosis both involve vascular obstruction of small hepatic arteries or portal branches and may progress to noncirrhotic portal hypertension. NRH is typically associated with systemic autoimmune diseases, hematological disorders and various drugs, particularly immunosuppressant and chemotherapeutic agents (29,30), whereas incomplete septal cirrhosis has been described in patients with viral hepatitis, alcoholism and exposure to vasculotoxic chemicals such as arsenic (31). Our patient did not have any of these conditions, nor was she on medication known to induce NRH or incomplete septal cirrhosis.…”
Section: Discussionmentioning
confidence: 81%
“…NRH and incomplete septal cirrhosis both involve vascular obstruction of small hepatic arteries or portal branches and may progress to noncirrhotic portal hypertension. NRH is typically associated with systemic autoimmune diseases, hematological disorders and various drugs, particularly immunosuppressant and chemotherapeutic agents (29,30), whereas incomplete septal cirrhosis has been described in patients with viral hepatitis, alcoholism and exposure to vasculotoxic chemicals such as arsenic (31). Our patient did not have any of these conditions, nor was she on medication known to induce NRH or incomplete septal cirrhosis.…”
Section: Discussionmentioning
confidence: 81%
“…Similar syndromes were reported from elsewhere in the world, and a variety of names including idiopathic portal hypertension, incomplete septal cirrhosis, hepatoportal sclerosis, nodular regenerative hyperplasia, partial nodular transformation and idiopathic noncirrhotic portal hypertension were used to describe these [4][5][6][7][8][9][10]. All these entities were characterized by intrahepatic portal hypertension that was not due to cirrhosis (when the definition of cirrhosis is applied rigorously) and where liver function remains preserved until a late date.…”
mentioning
confidence: 70%
“…12 Liver biopsy studies revealed a ISC frequency of 0.74-1.4%. 13 Histologically, it is characterized by of hepatic parenchyma nodularity, vascularized septa, reticulin buildup between hyperplastic parenchyma zones, sinusoidal dilatation and hepatocyte hyperplasia. 14 One of the pathophysiological mechanisms suggested was the existence of obliterative portal venopathy, with consequent heterogeneity in the hepatic parenchyma portal irrigation.…”
Section: Discussionmentioning
confidence: 99%